As relações entre a Arquivologia e a agenda 2030: mapeamento bibliográfico na Base de Dados em Ciência da Informação - Brapci - Gomes, Érica Patrícia (Brasil, 2024)
Due to the growing discussions and negative effects regarding the environmental impacts of human activity on the natural resources of planet Earth, this work proposes a bibliographic mapping in the Information Science Database - BRAPCI, where the aim was to identify the relationship established between Archival Science and the 2030 Agenda through the interpretation of authors who have already addressed the same topic. The general objective was to analyze initiatives to bring Archival Science closer to the 2030 Agenda of the United Nations - UN through a bibliographic survey in the Information Science Database. Its specific objectives included the identification of archival knowledge productions related to the 2030 Agenda indexed in the repository; Soon after, we sought to explore the data obtained from the publications collected; and, finally, understand the type of correlation established between Archival Science and the 2030 Agenda in the same publications. After carrying out the search by combining the corresponding keywords, 10 publications came in response, a sum that can be considered insignificant if one considers the relevance of the theme of sustainable development for a conscious professional practice aligned with the social needs of the present. Since the 2030 Agenda is a global agenda presented by the United Nations in 2015 that encompasses the environmental, economic and social axes and with a deadline for action until the year 2030 and Archival Science, a science that follows human evolution through the recording of information, realized It is understood that, opposing a possible conflict of interests, there is more affinity and that, if more investments, research and action plans are made in this affirmative relationship, it will be convenient and beneficial for everyone involved.